PRO DAN KONTRA TERHADAP KEBIJAKAN MANTAN NARAPIDANA KORUPSI DALAM PENCALONAN LEGISLATIF - Alvin Fauzi; Haryadi Haryadi (Universitas Airlangga, 2020)
his study discusses the prohibition of ex-corruption convicts who registered themselves as legislative candidates. Even this is supported by Article 7 paragraph 1 letter g PKPU. However, the Bawaslu (Election Oversight Body) allowed it and it is also supported by Yasonna Laoly, Minister of Justice and Human Rights of Indonesia, with the consideration that the regulations stipulated by PKPU contradict Law No. 7 of 2017 which states that ex-convicts are considered to have the same political rights as other citizens, a right guaranteed by the constitution. This study employs political contestation theory that explains the actions or processes that are disputed, for example ideological contestation on social policy, as well as political electoral theory that explains a system for making political decisions in which individuals gain the power to decide through competitive over people’s voices.